Deep venous thrombosis in pregnancy: incidence, pathogenesis and endovascular management - Devis, Paola; Knuttinen, M. Grace (Cardiovascular Diagnosis and Therapy, 2017)
Deep venous thrombosis (DVT) during pregnancy is associated with high mortality, morbidity, and costs. Pulmonary embolism (PE), its most feared complication, is the leading cause of maternal death in the developed world. DVT can also result in long-term complications that include postthrombotic syndrome (PTS) adding to its morbidity. Women are up to 5 times more likely to develop DVT when pregnant. The current standard of care for this condition is anticoagulation. This review discusses the epidemiology, pathogenesis, prophylaxis and diagnosis of DVT during pregnancy, and then focuses on endovascular treatment modalities. Inferior vena cava (IVC) filter placement and pharmacomechanical catheter directed thrombolysis (PCDT) in the pregnant patient are discussed, as well as patient selection criteria, and complications.